2016
DOI: 10.1089/brain.2015.0402
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Brain Tumor-Induced Neurovascular Uncoupling in Resting-State fMRI at Ultrahigh Field

Abstract: To demonstrate in a small case series for the first time the phenomenon of brain tumor-related neurovascular uncoupling (NVU) in resting-state blood oxygen level-dependent (BOLD) functional magnetic resonance imaging (fMRI) at ultrahigh field (7T). Two de novo (i.e., untreated) brain tumor patients underwent both BOLD resting-state fMRI (rsfMRI) on a 7T MRI system and motor task-based BOLD fMRI at 3T. Ipsilesional (i.e., ipsilateral to tumor or IL) and contralesional (i.e., contralateral to tumor or CL) region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…Very recently, a few publications (Agarwal et al, 2016a(Agarwal et al, , 2016bMallela et al, 2016) have demonstrated similar impaired BOLD responses in rsfMRI due to brain tumor-induced NVU. Studies by Agarwal et al (2016b) have demonstrated that tumor-related NVU can adversely affect the restingstate BOLD signal similar to its effect on task-based BOLD activation.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Very recently, a few publications (Agarwal et al, 2016a(Agarwal et al, , 2016bMallela et al, 2016) have demonstrated similar impaired BOLD responses in rsfMRI due to brain tumor-induced NVU. Studies by Agarwal et al (2016b) have demonstrated that tumor-related NVU can adversely affect the restingstate BOLD signal similar to its effect on task-based BOLD activation.…”
Section: Introductionmentioning
confidence: 90%
“…Another study demonstrated that brain tumor-related NVU may also similarly affect rsfMRI at ultrahigh field (7 Tesla) despite the higher signal-to-noise ratio afforded by higher field strength (Agarwal et al, 2016a). Mallela et al (2016) have examined the correlation of rsfMRI data with tumor characteristics and clinical information to characterize functional reorganization of resting-state networks (RSNs) and the limitations of this method in high-grade gliomas due to NVU.…”
Section: Introductionmentioning
confidence: 99%
“…51 Because of its easy implementation and less stringent requirements for patient compliance, rsfMRI has been attracting wide attention for use as a preoperative mapping tool. 52,53 However, rsfMRI also suffers from similar important clinical limitations of false negative BOLD signals due to brain-tumor related NVU; 5456 thus, to use rsfMRI as a reliable pre-surgical tool, it becomes all the more important to study NVU in cases of focal resectable brain lesions such as tumors to evaluate its effects on rsfMRI.…”
Section: Head Motion and Physiologic Noisementioning
confidence: 99%
“…In another study, they further assessed brain tumor-related NVU in rsfMRI at ultrahigh field (7T) and demonstrated that the higher SNR at 7T does not fully mitigate the effects of such NVU. 56 Mallela and colleagues examined the correlation of rsfMRI data with tumor characteristics and clinical information to characterize functional reorganization of RSNs and the limitations of rsfMRI in high-grade gliomas due to NVU. 54 …”
Section: Head Motion and Physiologic Noisementioning
confidence: 99%
“…A recent study in patients with brain tumors demonstrated only moderate group level rsfMRI versus tfMRI language network concordance with substantial subject‐level variability (Sair et al, ). Infiltration and abnormal neurovascular coupling, generally greater with higher tumor grade but also present in low‐grade gliomas (Pak et al, ), may compromise blood oxygenation level dependent (BOLD) contrast, both in rsfMRI and tfMRI (Hou et al, ; Jiang et al, ; Holodny et al, ; Agarwal et al, ).…”
Section: Introductionmentioning
confidence: 99%